Analisis Kemampuan Pemecahan Masalah Matematis Ditinjau Dari Kemandirian Belajar Siswa - Marwati Marwati (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2023)
The aim of this research was to analyse student’s mathematical problem solving abilities in terms of independent learning in rectangular material, specially squares and rectangles. This research is a qualitative descriptive study using a mixed method approach with data collection techniques using triangulation techniques. The data analyse technique was carried out through several stages, namely descriptive statistical analysis, data reduction stage, data presentation stage, and data verification. The subjects of this study were students of class VIII.2 UPTD SMP Negeri 4 Parepare. The test sheets were given directly to 22 students as subjects. Subjects will be selected as many as 3 students based on the results of the analysis of the answer sheets which are indicated to have problem solving abilities. The results of this study indicate that the ability to solve mathematical problems in class VIII.2 UPTD SMP Negeri 4 Parepare based on the independent learning indicator is in the medium category with a percentage of 59.66% with the first indicator, namely the ability to understand problems is in the medium category with a percentage of 52.53 %. The second indicator, namely the ability to determine a settlement plan, is in the very high category with a percentage of 96.21%. The third indicator, namely the ability to carry out the settlement plan, is in the high category with a percentage of 74.75%. The fourth indicator, namely the ability to check again, is in the very low category with a percentage of 15.15%.